(untitled) (Comparatismi, 2021)
Only a few decades ago, with computer technologies on the rise and the belief that only the so-called “hard sciences” would shape the lives of future generations, few would have imagined that stories and narratives would have not only maintained their central role in human societies, but would even reinforce it. Narration has been recently recognized as a universal feature of humanity, a meta-language capable of giving order to the reality and making us escape from the boundaries of space and time, representing at the same time both a need and a wish of every human being. Given its importance, why don’t we take care of our stories the same way we take care of our bodies? This is the goal of modern bibliotherapy, which puts into practice recent discoveries for the improvement of the homo narrans’ well-being.